Realization of the chess mate solver application - Vučković, V.V. (Yugoslav Journal of Operations Research; Vol 14 No 2 (2004): Vol. 14 No. 2, 2016)
This paper presents details of the chess mate solver application, which is a part of the author's Geniss general chess application. The problem chess is an important domain connected with solving of the chess problems. The Geniss Mate Solver (G.M.S.) application solves Mate-in-N-move problems. Main techniques used for the implementation of the application are full-width searching with Alpha-Beta pruning technique and zero evaluation function. The application is written in Delphi for Windows programming environment and the searching engine is completely coded in assembly language (about 10000 lines). This hybrid software structure enables efficient program development by using high-level programming environment and the realization of a very fast searching engine at the same time. The machine code is manually coded and could achieve above 7 million generated positions per second on the 1Ghz Celeron PC.